Development of Flipbook Based on Problem Based Learning on Ecosystem Materials to Train Student’s Scientific Literacy - Arika, Fadhila Zahra; Rachmadiarti, Fida (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2025)
Basically, the learning process for students is carried out in order to achieve learning outcomes with the help and encouragement of the teacher. Many teachers still use conventional methods in teaching, which can make students less interested and less motivated to learn. Thus, in order to optimize learning outcomes, teachers must use the latest approaches. This study aims to produce a flipbook based on Problem Based Learning on ecosystem material to train students' science literacy. The research method used is R&D (Research and Development). The flipbook based on Problem Based Learning on ecosystem material was tested on one class consisting of 30 students of class X SMAS Hang Tuah 4 Surabaya with a limited trial. The method used is the Four-D Model method. This study used student samples from two classes with different treatments. Data collection in this study consisted of validation techniques, observation, test, and questionnaire. The results showed that the validity of the flipbook reached 3.9 (very valid), the implementation of learning with flipbooks during classroom learning showed a value of 90% (very high category). This study shows that there are differences between classes X-5 and X-2 (t count 2.025> t table 2.003). The result of this study is that the treatment given to class X-5 gets a higher score and gets a score of 86.5 (value> 75) or above the minimun completeness criteria. The conclusion of this research is that flipbook are feasible and can be used in biology learning ecosystem material.